conteúdos identitários - Helder Carrasqueira (Dos Algarves)
The article examines the degree of internationalization of hotel companies, based on the assumption that high performance improves their competitive positioning and that of the regions in which they operate. Methodologically, we collected data characterizing hotel internationalization, insertion in international consortia, and the ability to attract international chains to the regions. Interviews with hotel directors were conducted. The results show that the Balearic region has the most internationalized companies. Madeira made an internationalization effort at the beginning of the 21st century; however, only the Pestana group has shown dynamism since then. The Algarve is competitive in attracting international brands but has the least successful level of international insertion. The comparative analysis shows that it is necessary to develop proactive measures that help prepare the future competitiveness of these regions through the internationalization of their companies. In addition, international chain hotels have been detected in consortiums. This positioning seems to be original in the literature, so we propose this line for investigation.